2020
DOI: 10.1016/j.jhazmat.2019.121569
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of phenol by Hydrilla verticillata (L.f.) Royle and associated effects on physiological parameters

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Similar enhancements in the MDA content of Azolla microphylla plants subjected to increasing concentrations of an insecticide -endosulfan have been shown to be related with the potential of this toxic compound to disturb the membrane stability (Raja et al, 2012a). In an aquatic species Chang et al (2020) observed that Hydrilla verticillata exposed to phenol shows an increased amount MDA content. Therefore, it is quite evident from our results that the phenolic compounds directly affect the membrane integrity of A. liculoides plants, especially at higher concentrations.…”
Section: Correlation Analysis Between the Concentration Of Phenols And The Other Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar enhancements in the MDA content of Azolla microphylla plants subjected to increasing concentrations of an insecticide -endosulfan have been shown to be related with the potential of this toxic compound to disturb the membrane stability (Raja et al, 2012a). In an aquatic species Chang et al (2020) observed that Hydrilla verticillata exposed to phenol shows an increased amount MDA content. Therefore, it is quite evident from our results that the phenolic compounds directly affect the membrane integrity of A. liculoides plants, especially at higher concentrations.…”
Section: Correlation Analysis Between the Concentration Of Phenols And The Other Parametersmentioning
confidence: 99%
“…After 3 days of treatment, exposure to external phenol was positively correlated with the increase of FNA, EL, MDA, total soluble sugar, SOD, APX, CAT, H 2 O 2 while, negatively correlated with RGR, RWC, chlorophyll a and b, and tissue phenol content ( (Chang et al, 2020, Lee et al, 2017, Zazouli et al, 2014, Stom and Roth, 1981. In the present study, the effect of different concentrations of phenol was evaluated on the performance of Azolla liculoides which is a commonly growing weed in the water bodies.…”
Section: Correlation Analysis Between the Concentration Of Phenols And The Other Parametersmentioning
confidence: 99%
See 1 more Smart Citation